The Sense of life satisfaction and aggressive behaviour of students of medical and non-medical universities - Brzezińska, Arleta (Journal of Education, Health and Sport, 2024)
The article presents the sense of life satisfaction and aggressive behaviors among students of medical and non-medical universities. The first part introduces the concepts of the sense of life satisfaction, sense of self-efficacy and aggressive behaviors and their components in the framework of Buss and Perry. The sense of life satisfaction was explored using The Satisfaction With Life Scale – SWLS, sense of self-efficacy by Generalized Self-Efficacy Scale – GSES and aggressive behaviors by Buss and Perry The Aggression Questionnaire – BPAQ. The group taking part in the study consisted of 213 people - 148 students of medical universities and 65 students of non-medical universities. Research results indicate that there is a relationship between life satisfaction and self-efficacy and the tendency towards aggressive behaviors. Respondents who experience greater life satisfaction and demonstrate higher levels of self-efficacy tend to exhibit lower tendencies towards aggressive behaviors. It was noticed that students of medical disciplines demonstrate a greater tendency towards aggressive behaviors in terms of expressing anger compared to students of non-medical disciplines.